2015
DOI: 10.1097/cin.0000000000000165
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Quality, Content, and Use of the Web Site Prepared for Family Members Giving Care to Stroke Patients

Abstract: This study was designed to evaluate the quality, content, usability, and efficacy of a Web site prepared for the purpose of improving the caregiving capability of family members who provide care for stroke survivors at home. The DISCERN score for the Web site was found to be 4.35 over 5. The first section that assesses reliability of the Web site was 4.38 over 5; mean score of the second section that measures the quality of the provided information on treatment/care options was 4.30, and mean score of the thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…This support could include information on medical or psychosocial issues, coping and managing, or healthy living, and in some cases internet links to related resources [32,33,35,[38][39][40][41]. In the case of stroke carers, there was comprehensive information on caring for a patient with stroke at home [41,42].…”
Section: Knowledge and Understandingmentioning
confidence: 99%
“…This support could include information on medical or psychosocial issues, coping and managing, or healthy living, and in some cases internet links to related resources [32,33,35,[38][39][40][41]. In the case of stroke carers, there was comprehensive information on caring for a patient with stroke at home [41,42].…”
Section: Knowledge and Understandingmentioning
confidence: 99%
“…Nevertheless, a review of the literature found no intervention study on caregivers' compassion fatigue. Although sharing experiences in an online group is an e cient and low-cost solution in supporting family caregivers (24), given that compassion fatigue is a concept that develops in family caregivers over time and due to long-term care of the elderly, these caregivers receive less social support and experiences shared by peer groups. Perhaps social support is needed to heal this objectivity that is rooted in perceived stress and di cult situations, mental and physical stress, and the grief of seeing a loved one suffering for a long time.…”
Section: Lynch Et Al (2018) Conducted a Study About Positive And Nega...mentioning
confidence: 99%